Risk - Stephen Webb (Social Work & Society, 2006)
Risk is a contestable, slippery and ambiguous concept making it very difficult to define. There are numerous definitions that depend on the situational context, field of application and adopted perspective. Risk is often normatively defined in probabilistic and mathematical terms as it relates to the expected losses which can be caused by a risky event and to the probability of this event happening. It is mapped to the probability of some event which is seen as undesirable. The harsher the loss, as it relates to the likelihood of the event, the worse the risk. This negative conception of risk as risk avoidance or risk aversion can be contrasted with a more positive account based on risk taking in venture capitalism and finance as a measure of the variance of possible outcomes. The systematic management of actuarial risk is called risk management. While the methodology for evaluating risk is called risk assessment. Techniques and methods for managing and assessing risk can vary considerably across different professions with the resultant effect that some professions, such as social work, are defined according to their ability and propensity to deal with risk. This has led Kemshall (2002) to argue that social work is predominantly concerned with handling and assessing risk, as opposed to focusing on social need and justice.